Designing the audience journey through repeated experiences - Benford, Steve; Greenhalgh, Chris; Hazzard, Adrian; Chamberlain, Alan; Kallionpää, Maria; Weigl, David M.; Page, Kevin R.; Lin, Mengdie (2018)
We report on the design, premiere and public evaluation of a multifaceted audience interface for a complex non-linear musical performance called Climb! which is particularly suited to being experienced more than once. This interface is designed to enable audiences to understand and appreciate the work, and integrates a physical instrument and staging, projected visuals, personal devices and an online archive. A public premiere concert comprising two performances of Climb! revealed how the audience reoriented to the second performance through growing understanding and comparison to the first. Using trajectories as an analytical framework for the audience ‘journey’ made apparent: how the trajectories of a single performance are embedded within the larger trajectories of a concert and the creative work as a whole; the distinctive demands of understanding and interpretation; and the potential of the archive in enabling appreciation across repeated performances.